CLIMATE NEUTRALITY: CONTEMPORARY CHALLENGES FOR EUROPEAN POLICY - Олена, Шевченко (Київський національний університет імені Т. Шевченка, 2024)
Вступ. У статті розглядаються питання викликів європейській кліматичній нейтральності, які постали перед Європейським Союзом через збройну агресію Росії в Україні. Автори підкреслюють, що Європейський Союз поставив перед собою амбітну мету стати першим у світі кліматично нейтральним континентом. Реалізація цих планів потребує скоординованої позиції не лише держав-членів, а й партнерів по ЄС. Військова агресія Росії проти України може вплинути на досягнення європейських кліматичних цілей, оскільки цей конфлікт супроводжується значним впливом на довкілля. Автори поставили за мету проаналізувати, як російське військове вторгнення в Україну може вплинути на досягнення кліматичного нейтралітету. Для досягнення мети були визначені наступні завдання дослідження, зокрема, охарактеризувати основні принципи стратегії та інструменти кліматичної політики ЄС, показати вплив російської агресії на екологію ЄС, визначити, чи тема екологічних наслідків російської агресії в Україні є актуальним для європейської громадськості та оцінити, як російська збройна агресія може вплинути на досягнення цілей європейської кліматичної нейтральності. Методи. Використовувалися такі методи: дискурсивний аналіз, аналіз документів, аналіз і синтез, порівняльний метод, контент-аналіз. Результати. У рамках дослідження було виявлено, що Європейський Союз прийняв низку документів, які фіксують цілі зеленого переходу, визначають інструменти їх досягнення та мають імперативний характер. Оскільки війна найбільше впливає на навколишнє середовище, європейська кліматична політика повинна буде враховувати екологічні наслідки, спричинені російською агресією в Україні. Є консенсус, що екологічна катастрофа в Україні, яка вже характеризується як екоцид, має комплексний характер і призведе до значного дисбалансу екосистем не лише в Україні, а й у Європі. Показано, що тема екологічних наслідків російського вторгнення в Україну для Європейського Союзу постійно присутня в європейських ЗМІ, що свідчить про її актуальність для європейської громадськості. Висновки. Аналіз екологічних наслідків військових дій дав змогу зробити висновок, що виклики європейській кліматичній політиці в досягненні цілей кліматичної нейтральності можна лише прогнозувати, тобто війна може як посилити кліматичну кризу, так і, відповідно, політичну викликів, а також покращити прогрес у реалізації «Зеленого курсу», що дозволить Європейському Союзу реалізувати свої кліматичні амбіції. З одного боку, очевидно, що війна посилює кліматичну кризу і, відповідно, політичні виклики. З іншого боку, за належного формату можна очікувати успіху в реалізації «Зеленого курсу», який дозволить Європейському Союзу вирішити свої специфічні завдання, зокрема стати першим кліматично нейтральним континентом, стимулювати глобальні кліматичні дії та підвищення конкурентоспроможності європейських економічних секторів. Відповідно, можна очікувати як більш амбітних кліматичних заходів, так і гальмування процесу.   Background. The article examines issues related to challenges to European climate neutrality, which have arisen before the European Union due to Russian armed aggression in Ukraine. The authors emphasize that the European Union has set an ambitious goal of becoming the world's first climate-neutral continent. The implementation of these plans requires a coordinated position not only of the member states, but also of the EU partners. Russia's military aggression against Ukraine may affect the achievement of European climate goals, as this conflict is accompanied by a significant impact on the environment. The authors set a goal to analyze how the Russian military invasion of Ukraine can affect the achievement of climate neutrality. To achieve the goal, the following research tasks were defined, in particular, to characterize the basic principles of the strategy and tools of the EU climate policy, to show the impact of Russian aggression on the ecology of the EU, to determine whether the topic of the environmental consequences of Russian aggression in Ukraine is relevant for the European public, and to assess how Russian armed aggression can influence the achievement of the goals of European climate neutrality. Methods. The following methods were used: discursive analysis, the analysis of the documents, analysis and synthesis, comparative method, content analysis. Results. In the frames of the study, it was revealed that the European Union has adopted a number of documents that fix the goals of the green transition, determine the tools for their achievement and are of an imperative nature. Since the war has the worst effect on the environment, the European climate policy will have to take into account the environmental consequences caused by the Russian aggression in Ukraine. There is a consensus that the ecological disaster in Ukraine, which is already characterized as ecocide, has a complex nature and will lead to a significant imbalance of ecosystems not only in Ukraine, but also in Europe. It is shown that the topic of the environmental consequences of the Russian invasion of Ukraine for the European Union is constantly present in the European media, which indicates its relevance for the European public. Conclusions. The analysis of the environmental consequences of military actions made it possible to conclude that the challenges to the European climate policy in achieving the goals of climate neutrality can only be predicted, that is, the war can both intensify the climate crisis and, accordingly, political challenges, and improve progress in the implementation of the "Green Course", which will allow the European Union to realize its climate ambitions. On the one hand, it is obvious that the war exacerbates the climate crisis and, accordingly, political challenges. On the other hand, with the proper format, we can expect success in the implementation of the "Green Course", which will allow the European Union to solve its specific tasks, in particular, to become the first climate-neutral continent, to stimulate global climate actions and to increase the competitiveness of European economic sectors. Accordingly, it can be expected both more ambitious climate actions and the inhibition of the process. Key words: climate neutrality, green transition, ecocide, Ukrainian-Russian war.

Background. The article examines issues related to challenges to European climate neutrality, which have arisen before the European Union due to Russian armed aggression in Ukraine. The authors emphasize that the European Union has set an ambitious goal of becoming the world's first climate-neutral continent. The implementation of these plans requires a coordinated position not only of the member states, but also of the EU partners. Russia's military aggression against Ukraine may affect the achievement of European climate goals, as this conflict is accompanied by a significant impact on the environment. The authors set a goal to analyze how the Russian military invasion of Ukraine can affect the achievement of climate neutrality. To achieve the goal, the following research tasks were defined, in particular, to characterize the basic principles of the strategy and tools of the EU climate policy, to show the impact of Russian aggression on the ecology of the EU, to determine whether the topic of the environmental consequences of Russian aggression in Ukraine is relevant for the European public, and to assess how Russian armed aggression can influence the achievement of the goals of European climate neutrality.
CLIMATE NEUTRALITY: CONTEMPORARY CHALLENGES FOR EUROPEAN POLICY
Keywords: кліматична нейтральність; зелений перехід; екоцид; українсько-російська війна; climate neutrality; green transition; ecocide; Ukrainian-Russian war; кліматична нейтральність; зелений перехід; екоцид; українсько-російська війна